WORLD STUDENT GAMES AS CULTURAL RESOURCE AND STUDENT COMMUNITY MOBILIZING FACTOR - Shurmanov, E.A.; Narkhov, D.Y.; Narkhova, E.N.; Dobrynin, I.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey the students’ motivations for the cultural resource mobilizing and contributions to the 2023 FISU World Student Games. Methods and structure of the study. We run, for the purposes of the study, a digital questionnaire survey (on CAVI platform, with the survey data mathematically processed by D.V. Shkurin using Vortex software tools) of a representative student sample (n=333); and analyzed contents of the personal accounts in the VKontakte social network (n=368) of students from 18 universities in the Sverdlovsk Oblast in December 2020 through January 2021. The survey and content analysis were designed to profile the values and priorities, personal and social problems, physical education and sports commitments, and attitudes to the 2023 FISU World Student Games, potential contributions and perceived regional and federal benefits of the event. Results and conclusion. One of the key conditions and factors for success of the upcoming major event is the commitment of the student community for preparations and hosting services, its interest and activity. The gender-specific survey data showed that women are apparently more interested in the international cooperation sensitive projects; men in the physical education and sports service infrastructure progress; with both of the gender groups equally interested in the youth physical education and sports encouragement initiatives. As for the negative and pessimistic opinions on physical education and sports on the whole and the 2023 World Student Games in particular, their origins need to be explored by special qualitative surveys. The 2023 World Student Games are expected to provide a great impetus for the sporting community and the national Sporting Life Norm project, and in general for the student cultural resource mobilizing initiatives in the homeland.